Decreased Circulating Klotho Levels in Patients Undergoing Dialysis and Relationship to Oxidative Stress and Inflammation. Issue 1 (January 2015) - Oh, Hyung Jung; Nam, Bo Young; Lee, Mi Jung; Kim, Chan Ho; Koo, Hyang Mo; Doh, Fa Mee; Han, Jae Hyun; Kim, Eun Jin; Han, Ji Suk; Park, Jung Tak; Yoo, Tae-Hyun; Kang, Shin-Wook; et al.
Introduction: It has been reported that klotho deficiency is associated with oxidative stress and inflammation in experimental kidney disease models. Patients with end-stage renal disease (ESRD) are particularly characterized by increased oxidative stress and inflammation. However, little is known about the relationship between these features and klotho in patients with ESRD. Methods: We conducted a single-center, cross-sectional study of 78 patients receiving peritoneal dialysis (PD). Serum concentrations of klotho, high-sensitivity C-reactive protein (hsCRP), interleukin-6 (IL-6), and 8-isoprostane were measured by enzyme-linked immunosorbent assay. To define factors independently associated with klotho, we determined Spearman's correlation coefficients for between co-variates and conducted multiple linear regression analyses. Results: Patients were classified by median concentration of klotho. In patients with klotho levels > 329.6 pg/mL, serum 8-isoprostane and IL-6 levels were significantly higher than in those with klotho levels < 329.6 pg/mL. In correlation analyses, log 8-isoprostane (γ = -0.310, p = 0.006) and log IL-6 (γ = -0.343, p = 0.002) were inversely correlated with log klotho. After adjustment for age, gender, mean arterial pressure, log intact parathyroid hormone, and log IL-6, log 8-isoprostane was independently associated with log klotho (β = -0.158, p = 0.040). However, the significant relationship between klotho and IL-6 was not seen in an adjusted model. Conclusions: This study showed that circulating klotho levels were significantly associated with 8-isoprostane levels in patients undergoing PD, suggesting a potential link between klotho deficiency and enhanced oxidative stress in ESRD patients.